The Investigation of Insulation Performance Evaluation of the Large Electrical Rotating Machine in Frequency Domain - Nattawut Phloymuk; Masaaki Kando; Norasage Pattanadech (My University, 2020)
The insulation structure of winding in a large electrical rotating machine consists of epoxy resin and mica material. The insulation structure is composed of many junctions. The insulation problems generate different kinds of signals, such as electromagnetic waves, which may get released from the non-perfect characteristics of the enclosure. This signal may interfere with the functioning of other nearby electronic devices. Therefore, maintaining an excellent condition of the insulation system of the machine is very important. For a condition monitoring of this insulation as proposed in this research, it is taken into consideration the results of the polarization and depolarization current (PDC) measurement of the test sample, and the stator winding rated 13.8 kV was investigated. The experiments were conducted under different thermal stresses, i.e., 25°C (the room temperature) and 100°C (the operation temperature). The test samples were divided into three types: I. haft-overhang, II. overhang and III. full stator bar. From the PDC measurement data record, the complex capacitance and polarization losses (ion migration polarization, slow relaxation polarization and interfacial polarization) were calculated. It was found that the aging of the insulation related to the complex capacitance and polarization losses can be contributed for research in future wireless technology.
Keywords: Insulation system; High voltage insulation and dielectric phenomena